The effect of Impact Angle on Dynamic Response of 19 Passenger Commuter Aircraft Windshield against Bird Strike - Warsiyanto, Budi Aji; Nurrohmad, Abian; Fitriansyah, Rizky; Utama, Agus Bayu; Sitompul, Sahril Afandi; Yuniarti, Endah (Indonesian Journal of Aerospace, 2021)
This paper's objective was to determine the dynamic response of a 19 passenger commuter aircraft windshield to impact angle variations. The phenomenon was performed using the finite element method, and the smoothed particle hydrodynamics (SPH) was chosen as a method for modeling bird material. The elastic-plastic polymethyl methacrylate (PMMA) material with the maximum principal strain failure criterion was used to model the windshield's dynamic response. The variation of the impact angle consists of 15°, 0°, -8°, and -15°, which are measured of the longitudinal axis of the aircraft. The simulation result showed that the impact angle that causes the windshield's dynamic response in the elastic, plastic deformation, and the greatest failure is the angle -15°. The upper end of the windshield (fixed) is the weakest part due to the stress concentration.